2014
DOI: 10.11646/zootaxa.3847.4.8
|View full text |Cite
|
Sign up to set email alerts
|

A fossil Paratrombiinae mite (Actinotrichida: Trombidioidea) from the Rovno amber, Ukraine

Abstract: The first description of a fossil representative of Paratrombiinae from the Rovno amber, Paratrombium rovniense sp. nov., based on an unengorged larva, is provided. The discovery results in a re-definition of the Paratrombiinae and of Paratrombium, which also comprise species with two pectinalae on coxa I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…If this scenario is correct, the ectoparasitism of non-mammalian vertebrates by chiggers that occurs today may be a product of secondary adaptation, as suggested by other authors [20]. Although the fossil record is devoid of trombidid mite specimens predating the Eocene [141], it has been speculated from palaeogeographical and comparative morphological evidence that trombiculid mites fed initially on other arthropods, with larval ectoparasitism on vertebrates evolving during the Paleocene, leading to an increase in chigger diversity [20]. Our data challenges this hypothesis, because it implies that something other than host choice in the larval stage drove the split between the Trombidioidea and the Trombiculoidea 60 million years before the latter began feeding on vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…If this scenario is correct, the ectoparasitism of non-mammalian vertebrates by chiggers that occurs today may be a product of secondary adaptation, as suggested by other authors [20]. Although the fossil record is devoid of trombidid mite specimens predating the Eocene [141], it has been speculated from palaeogeographical and comparative morphological evidence that trombiculid mites fed initially on other arthropods, with larval ectoparasitism on vertebrates evolving during the Paleocene, leading to an increase in chigger diversity [20]. Our data challenges this hypothesis, because it implies that something other than host choice in the larval stage drove the split between the Trombidioidea and the Trombiculoidea 60 million years before the latter began feeding on vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Increased research on fossil arachnids in recent years (Penney 2016;Dunlop et al 2018a) has resulted in a significant increase in the number of described terrestrial Parasitengona mites (Konikiewicz & Mąkol 2014, and data summarized therein; Bartel et al 2015;Konikiewicz et al 2016aKonikiewicz et al , 2016bDunlop et al 2018b;Mąkol et al 2018). Representatives of nine out of 19 families currently assigned to terrestrial parasitengones (Mąkol & Wohltmann 2012) have been recorded from the Cretaceous, and/or Paleogene deposits.…”
Section: Introductionmentioning
confidence: 99%
“…From a total of 1828 species, it was reported that 808 are known only from larvae, 889 from active postlarval forms and 131 from both. Since 2013, 35 species have been described, of which 29 are known only from larvae, 2 from active postlarval forms and 4 from both (Sevsay & Karakurt, 2013a, b;Adil & Sevsay, 2014a, b;Mahmoudi et al, 2014;Mąkol & Sevsay, 2014;Konikiewicz & Mąkol, 2014;Kamran & Alatawi, 2014Adil et al, 2015 a, b, c, d;Karakurt & Sevsay, 2015;Karakurt et al, 2016;Mayoral & Seeman, 2015;Masoumi et al, 2016;Noei et al, 2014;Noei et al, 2015 a, b, c;Noei et al, 2017;Haitlinger & Šundić, 2015 a, b, c, d;Šundić & Haitlinger, 2015 a, b;Haitlinger et al, 2016;Konikiewicz et al, 2016;Liu & Zhang, 2016;Yazdanpanah et al, 2016;Mayoral & Barranco, 2017;Saboori et al, 2017).…”
Section: Introductionmentioning
confidence: 99%